Writing as Design: Enabling access to academic discourse in a multimodal environment - Archer, Arlene (South African Journal of Higher Education, 2016)
This paper builds on and contributes to work in writing pedagogy, with a particular focus on multimodality. Research on writing and academic literacies have examined changing texts in higher education, yet there has not been a particular emphasis on how these texts are reconfigured in the multimodal moment. This paper examines the implications of a more inclusive view of the representational landscape for writing pedagogies and academic literacies. It explores the visual nature of writing, and some of the ways academic discourse is constructed across images and writing in texts in Higher Education. It also questions the extent to which visual and verbal modes can be used as critical ‘metaforms’ for reflection. The aim is to create awareness in order to enable student access to a broader multimodal notion of academic discourse.